2019
DOI: 10.3389/fpls.2019.01242
|View full text |Cite
|
Sign up to set email alerts
|

Wheat F-box Protein TaFBA1 Positively Regulates Plant Drought Tolerance but Negatively Regulates Stomatal Closure

Abstract: The phytohormone abscisic acid (ABA) regulates plant growth and development, as well as responses to various stresses, such as salt and drought. The wheat TaFBA1 gene, which encodes an F-box protein, was previously identified in our laboratory by homologous cloning. We previously found that TaFBA1 expression was induced by ABA and drought stress. In this study, wild-type (WT), TaFBA1 over-expressing (OEs), TaFBA1 homologous gene mutants, and TaFBA1 recovery (Rs) Arabidopsis plants were used. We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 65 publications
(88 reference statements)
1
21
0
1
Order By: Relevance
“…The top most significantly associated SNP (S8_60346825), on chromosome 8, was located 2 kb from Srp40 (Serine/Arginine‐rich proteins ) which was previously reported to contribute to plant‐specific forms of developmental regulation and environmental adaptation (Califice, Baurain, Hanikenne, & Motte, 2012). Four other candidate genes encoding F‐box proteins , Auxin response factor 22, Pyrophosphate‐energized vacuolar membrane proton pump (EC 3.6.1.1) , and Ferritin 2 proteins were reported to mediate auxin action in biotic and abiotic stress responses, regulation of salt and drought stress tolerance and protection against oxidative stress (An et al., 2019; Bouzroud et al., 2018; Briat et al., 2010; Fukuda, Chiba, Maeda, Nakamura, & Maeshima, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The top most significantly associated SNP (S8_60346825), on chromosome 8, was located 2 kb from Srp40 (Serine/Arginine‐rich proteins ) which was previously reported to contribute to plant‐specific forms of developmental regulation and environmental adaptation (Califice, Baurain, Hanikenne, & Motte, 2012). Four other candidate genes encoding F‐box proteins , Auxin response factor 22, Pyrophosphate‐energized vacuolar membrane proton pump (EC 3.6.1.1) , and Ferritin 2 proteins were reported to mediate auxin action in biotic and abiotic stress responses, regulation of salt and drought stress tolerance and protection against oxidative stress (An et al., 2019; Bouzroud et al., 2018; Briat et al., 2010; Fukuda, Chiba, Maeda, Nakamura, & Maeshima, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…F-box proteins play regulatory roles in protein degradation through the proteolytic mechanism of multi-protein E3 ubiquitin ligase in response to cellular signals during plant development and growth, hormone responses, and biotic/abiotic stress responses [ 2 ]. For example, in wheat, the TaFBA1 F-box protein with a FBA domain has been implicated in drought tolerance [ 37 ], whereas the F-box protein TaJAZ1 regulates resistance against powdery mildew [ 38 ], and the cyclin F-box domain TaCFBD gene is involved in inflorescence development and cold stress responses [ 39 ]. To date, however, a functional analysis of wheat F-box genes was conducted at the single gene level despite the important roles in several aspects of plant abiotic/biotic stress and development.…”
Section: Discussionmentioning
confidence: 99%
“…An F-box gene, TaFBA1 , was identified in wheat organs, including roots [ 57 ]. In other few studies, overexpression of the gene showed drought tolerance, oxidative stress tolerance, heat tolerance, and longer root lengths relative to wild-genotype transgenic tobacco and Arabidopsis [ 56 , 57 , 58 , 59 ]. In rice, overexpression of MAIF1 improved abiotic stress tolerance and helped to control root growth through multiple signal pathways, including negative signaling with abscisic acid (ABA), auxin, and ABA interactions, and the sucrose signaling pathway [ 62 ].…”
Section: Discussionmentioning
confidence: 99%